If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10x + -6 = 9x + 1 Reorder the terms: -6 + 10x = 9x + 1 Reorder the terms: -6 + 10x = 1 + 9x Solving -6 + 10x = 1 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. -6 + 10x + -9x = 1 + 9x + -9x Combine like terms: 10x + -9x = 1x -6 + 1x = 1 + 9x + -9x Combine like terms: 9x + -9x = 0 -6 + 1x = 1 + 0 -6 + 1x = 1 Add '6' to each side of the equation. -6 + 6 + 1x = 1 + 6 Combine like terms: -6 + 6 = 0 0 + 1x = 1 + 6 1x = 1 + 6 Combine like terms: 1 + 6 = 7 1x = 7 Divide each side by '1'. x = 7 Simplifying x = 7
| Y=.23x+.55 | | 343x^3= | | X^4-x^2=400 | | 3(4p+1)-2(p-5)= | | Y=.23+.55 | | X+.75x=140 | | x^2+169x+26=19 | | 4x^4+5x^2=8 | | x^2-10x-25=14 | | 8+3x-x=6 | | 21=w^2+4w | | 30=-x+100 | | (-3x-7)+(4x+7)=0 | | Tanx*cotx= | | 3x^2-4x+150=0 | | 2x*3x=10*(10x+10) | | 1/3x-15/120x= | | 0=2x^2+11x+21 | | -7(7x-3)+1=-49x+22 | | 22x-45=93 | | 0.75(2x-5)=0.50(x+2) | | 2x-4=3(x+6) | | X(x+3x)=8(8+(x+2)) | | 64-x=73-2x | | log[4]2*x=0 | | a(7x+3)=b-21x | | y-4=30 | | 7*49=x*8x | | (x^2-1)+2(x^2-1)-15=0 | | 55=-0.8x+72 | | 0=x^2-12x+40 | | 2w^2-3w=5 |